Prostate artery embolization: a new, minimally invasive treatment for lower urinary tract symptoms secondary to prostate enlargement. (August 2017) - Maclean, Drew; Maher, Ben; Modi, Sachin; Harris, Mark; Dyer, Jonathan; Somani, Bhaskar; Hacking, Nigel; Bryant, Timothy
Prostate artery embolization (PAE) is emerging as a safe and efficacious treatment which approaches benign prostatic obstruction (BPO) from a unique perspective. This brings with it distinct advantages and solutions, which we discuss along with cost, evidence, complications and disadvantages.